Versatile boron‐based thermally activated delayed fluorescence materials for organic light‐emitting diodes - Han, Jianmei; Chen, Yanying; Li, Nengquan; Huang, Zhongyan; Yang, Chuluo (Aggregate (Hoboken), 2022)
During the last few years, organoboron‐based thermally activated delayed fluorescence (TADF) materials have received extensive attention in optoelectronic area, owing to the unique electronegativity of boron atom. Herein, many research progress of organoboron‐based TADF materials for organic optoelectronic devices is summarized. This review comprehensively documents the organoboron‐based TADF materials according to the emission colors from blue to red‐near‐infrared (red‐NIR), covering the molecular design strategies, photophysical properties, and optoelectronic performance in organic light‐emitting diodes (OLEDs). The current progress and future challenges in this fast‐growing fields are reviewed systematically, providing instructive guidance for the future research on high‐performance TADF‐OLEDs. Recent progress on versatile boron‐based thermally activated delayed fluorescence materials for organic light‐emitting diodes is systematically summarized according to the emission colors, covering the molecular design strategies, photophysical properties, and optoelectronic performance in the organic light‐emitting diodes. The current challenges and future directions in this rapidly growing field are commented.